A MODIFIED CAESAR CIPHER ENCRYPTION TECHNIQUE FOR SECURED INFORMATION SHARING - Olanrewaju, Babatunde Seyi; Eguavoen, Victor Osasu; Okunade, Oluwasogo Adekunle (FUDMA JOURNAL OF SCIENCES, 2025)
The need to ensure the confidentiality of data in a shared environment triggered the implementation of cryptography, where data is transformed into an unintelligible format. In modern cryptography, complex mathematical concepts create a strong encryption system. This paper developed an encryption method based on the Caesar cipher method. The developed method modified the Caesar cipher method by adding a second layer of encryption. In the developed method, after the first encryption using the Caesar cipher substitution method, an alphanumeric table for Caesar cipher text was formulated to generate the final cipher text, which leaves no resemblance to the Caesar cipher encryption. The encryption was implemented using the Python programming language. Both the Caesar cipher and the modified methods were simulated in a Python Integrated Development Environment and tested using a brute force attack. The results showed the Caesar cipher method broken without the shift key available, while the modified method could not be broken. The result demonstrated that a strong encryption technique could be developed with less complexity.